MANAGEMENT CONSULTING AS AN INSTITUTIONAL TOOL FOR OVERCOMING BARRIERS TO THE DEVELOPMENT OF SMALL AND MEDIUM-SIZED ENTERPRISES IN COMPLEXLY REGULATED MARKETS A CASE STUDY OF THE BEAUTY INDUSTRY - Блажко, Катерина (SWorldJournal, 2026)
This article presents a conceptual and analytical study of the transformation of the role of management consulting in the context of small and medium-sized enterprise development in highly regulated service markets. Using the beauty industry as a case stu